Effects of Spironolactone on Arrhythmias in Hemodialysis Patients: Secondary Results of the SPin-D Randomized Controlled Trial. Issue 4 (10th April 2023) - Mc Causland, Finnian R.; Hsu, Jesse Y.; Himmelfarb, Jonathan; Ikizler, Talat Alp; Raj, Dominic S.; Mehrotra, Rajnish; Waikar, Sushrut S.; Kimmel, Paul L.; Kliger, Alan S.; Dember, Laura M.; Charytan, David M.
Abstract : Abstract : Key Points: The effects of spironolactone on arrhythmia in patients receiving maintenance hemodialysis are unclear. In these post hoc analyses, spironolactone resulted in a higher frequency of bradycardia and conduction blocks, compared with placebo. Close monitoring may be warranted for patients on maintenance hemodialysis receiving MRAs, while definitive trial results are awaited. Background: Patients receiving maintenance hemodialysis (HD) have a high incidence of cardiovascular events, including arrhythmia and sudden death. Spironolactone reduces the risk of cardiovascular events and sudden death in patients with heart failure, but the effects of spironolactone on arrhythmic events in patients treated with maintenance HD are unclear. Methods: The Safety and Cardiovascular Efficacy of Spironolactone in Dialysis-Dependent ESRD (SPin-D) trial was a 36-week randomized, placebo-controlled, double-blind trial comparing three different doses of spironolactone with placebo in maintenance HD patients. We performed a post hoc analysis in a subset ( n =57) who underwent extended electrocardiographic monitoring using a wearable device at baseline and follow-up. Generalized estimating equations models were fit to determine the associations of spironolactone (individual doses and combined) versus placebo on the incidence rate of predefined categories of arrhythmic events. Results: The average age of participants was 55±12 years, 61% were male, and 77% were Black. The overall proportion of patients with at least one arrhythmia event was 43% (15/35) at baseline and 81% (43/53) at the end of follow-up. At the end of follow-up, the rate of bradycardic events or conduction blocks was higher in the combined spironolactone group, compared with placebo (82.4 versus 38.7 events/100 patient-days; P <0.001). Similar findings were noted in adjusted models, but did not meet statistical significance (adjusted rate ratio of 2.04; 95% confidence interval 0.83–5.05). Conclusions: In a 36-week trial of patients receiving maintenance HD, a higher frequency of bradycardia and conduction blocks was observed among those treated with spironolactone treatment compared with placebo. Larger studies are required to investigate the longer-term effects of spironolactone on cardiac conduction in patients receiving HD.